Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species - Sirenko, Boris; Sellanes, Javier (Zootaxa, 2016)
We update the list of the bathyal chitons of the genus Leptochiton inhabiting Chilean waters. We report new records of Leptochiton belknapi and L. laurae, the first record of L. sigwartae for the area and the new species L. ibanezi sp. nov. and L. ferreirai sp. nov. With 12 species, including those described herein as new, the highest species richness of Leptochiton is found in Chilean deep waters. Taking into consideration the potential late Paleozoic origin of the genus Leptochiton, we propose that Leptochiton originated in the old Pacific Ocean and migrated to the young Atlantic Ocean. However, the genus has also been considered non-monophyletic.